A long cavity passive mode-locking fibre laser with the reflective non-linear optical loop mirror. Issue 2 (19th January 2017) - Wang, Pinghe; Tang, Yibiao; Peng, Hanlin; Shi, Guohua; He, Tiejun; Li, Heping; Liu, Yong
Abstract: In this paper, we report a long cavity passively mode-locked fibre laser. The proposed mode locker is a reflective long cavity non-linear optical loop mirror (NOLM) which consists of a 50:50 coupler and 2-km single-mode fibres. The laser achieves stable mode locking at a fundamental repetition rate of 100 kHz. The rectangular pulses operating in dissipative soliton resonance region is generated in the laser. The relationship between the pulse duration and the pump power is investigated in detail. When the pump power is 200 mW, the laser generates rectangular pulses at 1565.57 nm (central wavelength) with pulse duration of 81.5 ns. The single pulse energy as high as 33.34 nJ is obtained. The results show that the reflective NOLM is an efficient mode locker and useful for the generation of high energy pulse.